The role of freight transport in economic development: An analysis of the interaction between global value chains and their associated transport chains - Poul Ove Pedersen (Danish Institute for International Studies (DIIS), 2007)
The purpose of this paper is first to discuss the paradox that freight transport, which so clearly is an important prerequisite for the processes of regional development and economic international-isation and globalisation, since the 1970s has almost vanished from mainstream economic geo-graphy and development studies, and is most often hardly mentioned in studies of international industrial development and global commodity or value chains. Secondly, the paper discusses the consequences of leaving freight transport out of the value chain analyses and argues that it has had serious consequences for economic development especially in the peripheral parts of the world, not least in Africa, and for our understanding of rural poverty. – – Formålet med dette papir er først at diskutere det paradoks, at godstransport - der så klart er en vigtig forudsætning for økonomisk regional udvikling, internationalisering og globalisering - stort set er forsvundet fra økonomisk geografi og udviklingsstudier, og meget sjældent behandles i stu-dier af international industriudvikling og globale vare- og værdikæder. For det andet diskuterer papiret konsekvenserne af ikke at inddrage overvejelser om godstransporten og dens organisering i de globale vare- og værdikædeanalyser, og det konkluderes, at det har haft alvorlige konsekven-ser for den økonomiske udvikling i de perifere dele af verden, ikke mindst i Afrika, og for vores forståelse af fattigdommen i ulandenes landdistrikter.
Keywords: 330; Transportkosten; Betriebliche Wertschöpfung; Entwicklung; Ländliche Armut; Agrarprodukt; Afrika